Mapping nociceptive stimuli in a peripersonal frame of reference: evidence from a temporal order judgment task. - De Paepe, A; Crombez, G; Spence, C; Legrain, V (2014)
The ability to localize nociceptive stimuli on the body surface is essential for an organism to respond appropriately to potential physical threats. This ability not only requires a representation of the space of the observer׳s body, but also of the external space with respect to their body. Therefore, localizing nociceptive stimuli requires coordinating multiple senses into an integrated frame of reference. The peripersonal frame of reference allows for the coding of the position of somatosensory stimuli on the body surface and the position of stimuli occurring close to the body (e.g., visual stimuli). Intensively studied for touch, this topic has been largely ignored when it comes to nociception. Here, we investigated, using a temporal order judgment task, whether the spatial perception of nociceptive stimuli is coordinated with that of proximal visual stimuli into an integrated representation of peripersonal space. Participants judged which of two nociceptive stimuli, one presented to either hand, had been presented first. Each pair of nociceptive stimuli was preceded by lateralized visual cues presented either unilaterally or bilaterally, and either close to, or far from, the participant׳s body. The perception of nociceptive stimuli was biased in favor of the stimulus delivered on the hand adjacent to the unilateral visual cue, especially when the cue was presented near the participant׳s hand. These results therefore suggest that a peripersonal frame of reference is used to map the position of nociceptive stimuli in multisensory space. We propose that peripersonal space constitutes a kind of margin of safety around the body to alert an organism to possible threats.